The self-efficacy for coping and quality of life women with breast cancer in Hospital Universiti Malaysia - Ali, Rodziah (2015)
Introduction: Breast cancer is the second most common cancer in the world and the commonest cancer in Malaysia. High level of self-efficacy for coping in breast cancer survivors has a positive effect on health behaviors, symptom control, compliance with cancer treatment, as well as on quality of life (QoL). This study aims to determine the self-efficacy for coping scores and its association with socio-demographic and clinical variables. As well as to determine the global, functional and symptoms QoL and its correlation with self-efficacy for coping within 3 years of diagnosis in breast cancer women in Hospital Universiti Sains Malaysia. Methodology: This is a cross sectional study involving 168 women diagnosed with breast cancer between January 1, 2009 and December 31, 2012. The universal sampling method was applied following inclusion and exclusion criteria recruited from January 2012 to December 2012. The inclusion criteria were age >18 years old, histologically confirmed breast cancer and cancer was diagnosed from January 2009 until December 2012. The exclusion criteria were illiterate and diagnosed with cognitive impairment. A self-administered/self-guided questionnaire used to obtain the socio-demographic and clinical characteristics, self-efficacy for coping and QoL. The brief Cancer Behavior inventory (CBI-B) and the European Organization for Research and Treatment of Cancer (EORTC) with breast cancer’s questionnaires were used. Patients’ medical record was used for detail information about medical/clinical data. The data were analyzed by using multiple linear regressions and Spearman rank correlation Result: The mean score of self-efficacy for coping in breast cancer women was 83.67 (95% CI: 81.87, 85.47). The positive impact on self-efficacy for coping were higher educational levels (β=7.26, p<0.001) and good income (β=0.001, p=0.021). However, positive family history of breast cancer (β=-5.43, p=0.008), and performed breast cancer surgery (β=-16.44, p=0.003) reduced the self-efficacy for coping. The mean of global QoL was 59.9 (95% CI 56.7, 63.0). The global QoL (r=0.407 p<0.001), and functioning QoL subscales (r ranged from 0.191 to 0.308, p<0.05) were significant positive correlation with self-efficacy for coping, but symptoms QoL subscales (r ranged from -0.157 to -0.282, p<0.05) had significant negative correlation with selfefficacy for coping. Conclusion: The self-efficacy for coping mean score was moderate in breast cancer women. Higher educational levels and good income increased the self-efficacy for coping. However, positive family history of breast cancer and breast cancer surgery reduced the self-efficacy for coping. The global QOL mean score was slightly below average in this study and the functional QoL had a significant positive correlation with self-efficacy for coping. But, symptoms QOL had a significant negative correlation with self-efficacy for coping.